TEACHING FOOD VOCABULARY TO (YOUNG LEARNERS) THROUGH INTERACTIVE ACTIVITIES - Qosimova Saida Umidjon qizi; Gaziyeva Saida (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstact   Early vocabulary acquisition is crucial to language learning, particularly for young students who are still developing their linguistic and cognitive abilities.  Food-related  vocabulary  is  perfect  for  early  vocabulary  education  since  it  is  particularly relevant to children's everyday lives and is also simpler to visualise and contextualise.  In  this  study,  children  ages  4  to  7  in  a  kindergarten  setting  will  be  taught  food terminology through interactive activities, including games, songs, role-plays, visual aids, and physical reaction tasks.  Using a qualitative classroom-based methodology, the  study  involves  15  preschoolers  over  a  four-week  period.  Every  week,  students encountered a range of interactive exercises created especially to teach a certain group of vocabulary words related to food.  Informal learner feedback, vocabulary checklists, and  instructor  observations  were  used  to  gather  data.    The  results  showed  that interactive exercises greatly improved learner motivation, pronunciation accuracy, and vocabulary retention.  Compared to typical rote-learning approaches, children showed improved  memory,  more  confidence  in  utilising  new  terms,  and  more  active engagement  in  classes.    According  to  the  study's  findings,  interactive  teaching techniques  are  very  successful  and  ought  to  be  incorporated  into  early  language education programs on a regular basis.  For ESL teachers, curriculum designers, and educators working with young learners, this research offers insightful information and useful tactics for improving the effectiveness, engagement, and meaning of language learning.